«Den sletteste, den nedrigste og uretfærdigste Embeds Mand» Om prosessen mot byfogd og politimester i Christiansand Mauritz Antonius Schweder - Geir Heivoll (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The first Norwegian Chiefs of Police were appointed in the four main cities during the latter part of the 1600s. The first office was established in Trondheim in 1686, then Bergen in 1692, Christiania in 1744, and finally Christiansand in 1767.